Cross disorder homogeneity: An examination of neurodevelopmental disorders through behavioural correlates and functional connectivity - Abdel-Baki, Rita (My University, 2017)
Over 300,000 children in Ontario are diagnosed with neurodevelopmental disorders, which are defined as mental disorders with an onset in the developmental period. Autism spectrum disorder (ASD), attention-deficit hyperactivity disorder (ADHD), and obsessive-compulsive disorder (OCD) are three neurodevelopmental disorders with symptom overlap including difficulties with social skills, inattention, and behavioural flexibility. The National Institute of Mental Health (NIMH) proposed the Research Domain Criteria (RDoC) to address these overlaps by examining symptoms at a biological, as well as observable, level. This study investigated how children with diagnoses of ASD (n=90), ADHD (n=47), and OCD (n=32) group together based on their symptom scores on the Social Communication Questionnaire (SCQ), the inattention subscales of the Child Behaviour Checklist (CBCL), and the behaviour flexibility subscales of the Repetitive-Behaviour Scale-Revised (RBS-R). Correlations between cluster groupings and functional connectivity were then evaluated. Children were clustered into 3 groups: (1) a group characterized by high inattention; (2) a group characterized by moderate impairment across social skills, inattention, and behavioural flexibility; and (3) a group characterized by high impairment in all measures. Functional connectivity between the anterior cingulate cortex and intraparietal sulcus was positively correlated with symptom scores on behavioural flexibility in group 1. Connectivity between the right amygdala and both the left superior temporal gyrus and the lateral parietal region were negatively correlated with symptom scores on behavioural flexibility in group 3. This study was the first to collapse across diagnostic groups of neurodevelopmental disorders, and examine the correlation between symptom severity and functional connectivity. Findings support the use of the RDoC framework.